Empire and the Christian Tradition : New Readings of Classical Theologians - Rieger, Joerg; Kwok, Pui-lan; Compier, Don H. (Book collections on Project MUSE., 2007)
Distinguished theologians assess the achievements and legacies of 31 theological giants in light of Christianity's engagement with imperial power, conquest, colonization, and post colonial themes.